Optical properties of zinc oxide thin film fabricated by spraying deposition method. Issue 2 (June 2021) - Sulhadi,; Muqoyyanah,; Darsono, T; Wahyuni, S; Sugianto,; Marwoto, P
Abstract: Zinc oxide (ZnO) is a semiconductor material which commonly used for optoelectronic devices due to its several advantages. Various ZnO thin film synthesis or fabrication method have widely developed to produce the desired material with excellent properties, such as low resistivity, high transmittance, and simpler experiment procedures. This work focused on the utilization of spraying deposition as a new method to fabricate ZnO thin film. Based on UV-Vis measurement, all of the fabricated ZnO thin films presented high transmittance over 80%. In addition, the optimum spraying distance was found to be 20 cm which resulted transmittance and Eg value of 98.6% and 3.95 eV, respectively. This method presented a lower cost and simpler method to fabricate ZnO thin film.